Indonesia : Fourth Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report, 2006)
Indonesia's Fourth Post-Program Monitoring discussions highlight that short-term macroeconomic indicators and near-term prospects have deteriorated. Financial sector vulnerabilities have increased in the face of rising interest rates and a slowing economy, but the overall banking sector remains resilient to moderate credit, interest, and depreciation risks. Improved budget execution could help cushion the downturn. Reducing delays in disbursing funds to executing agencies and better project implementation would help offset the expected decline in private consumption.